EVUALATING FILTER ELEMENT OPERATION EFFICIENCY AND MONITORING CONTENT IN THEM MECHANICAL IMPURITY FROM AVIATION FUEL - M. L. Nemchikov; E. A. Konyaev; A. N. Kozlov; K. I. Gryadunov (Научный вестник МГТУ ГА, 2016)
The article provides the research results of the mechanical impurity composition and concentration from the dif- ferent layers of standard filter element Fuel monitor Velcon CDF 230 F, removed from the fueller in order to evualate its operation efficiency and equipment resource forecasting capabilities of X-ray fluorescence analyzer ADC “Prizma”.